Membuat Portofolio Pribadi Menarik dalam Mempersiapkan Diri Melamar Pekerjaan bagi Orang Muda Binaan Marga Sejahtera - Dwi Ananto Pamungkas, Petrus; Hendrik Maturbongs, Yoseph; Koesmaryanto Oetomo, R. (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2021)
Portfolio is one of the main administrative requirements if someone wants to apply for a job. In a portfolio you can see what and how a person is. In this training, participants are invited to directly practice on making attractive portfolios so that they have the opportunity to be accepted by the company. Even though using the zoom meeting media, participants can still practice directly according to the instructions from the lecturer team as a training supervisor. With time constraints and some participants experiencing problems related to internet connection, the training supervisor team provided portfolio creation materials by utilizing the templates available in the document management application. The great enthusiasm of the participants made the training supervisor team even more enthusiastic, especially the continuation of mentoring through the email media of the training supervisor team. In a short time, we were able to produce several examples of participant portfolios sourced from supporting documents, such as diplomas and certificates as well as experiences.